Identification of Landslide-Prone Areas in Sanggau Regency, West Kalimantan using GIS and Resistivity Method - Radhitya Perdhana; Nurhasanah Nurhasanah; Riza Adriat (Jurnal Fisika Flux: Jurnal Ilmiah Fisika FMIPA Universitas Lambung Mangkurat, 2023)
Currently, the weather in Indonesia has been greatly affected by climate change. This is evidenced by extreme weather events in early 2020 which are predicted to occur more frequently in Indonesia. Bad weather in the form of high rainfall will potentially cause hydrometeorological disasters such as floods and landslides. To anticipate the occurrence of landslides that have the potential to disrupt regional development, it is important to conduct research to map landslide-prone areas in the province of West Kalimantan. This research is in line with UNTAN's strategic research plan to contribute to disaster management and climate change. This research combines overlay and measurement methods with geoelectric methods. The overlay method is used as a method to map landslide susceptibility based on scoring calculations from land parameters. The mapping is expected to produce a map of the landslide-prone zone which can then be studied further. Assessment of landslide potential through slip plane analysis using resistivity geoelectric method. From the mapping and direct observation, it is proved that the high landslide susceptibility values correlate with the landslide occurrence in Sabang Merah, Sanggau. Based on the resistivity measurement there found the potential landslide slip surface that is connected with the dip of rock layers in the area.